Analisis Kelayakan Usaha Gula Aren di Kelompok Tani Tanisari Desa Ngargosari Kecamatan Loano Kabupaten Purworejo - Fatmawati, Nurlaila; Alim, M Abdul Rohman; Barokah, Umi; Nugroho, Rahmat Joko; Muflih, Ghufron Zaida (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Ngargosari Village is one of the palm sugar producing villages in Loano District. The palm trees in Ngargosari Village are not cultivated; they grow naturally and are cultivated through generations, with the number of palm trees reaching 3,000. This study aims to determine the business analysis of costs, revenue, income, as well as the feasibility analysis of R/C and BEP (BEP unit and price) of palm sugar production per month in the